Makam Raden Maoneng di Kabupaten Pemalang : Tinjauan Berdasarkan Aspek Sejarah dan Fungsinya - Leni Agustina; Isna Yulda Yanu Anugraj; Sofiroh (JSI: Jurnal Sejarah Islam, 2023)
This article aims to explain the history and function of Raden Maoneng's tomb for the people of Pemalang Regency. The theory used in this research is structuralfunctional. The data in this study were obtained from study interviews and literature. The results of this study can reveal: first, the history of Raden Maoneng according to oral tradition has been in Pemalang since the 16th-17th century. Raden Maoneng himself is the son of a Madiun Regent named Purbaya who will carry out the pilgrimage to Mecca. However, before the journey began his father advised him to pass through Pemalang Harbor and stop there temporarily. After a long stay in Pemalang and going through several events, Raden Maoneng became a figure who played an important role in Pemalang Regency, so it's no wonder his grave was designated as a cultural heritage and has its own function for the people of Pemalang Regency. secondly, Raden Maoneng's tomb functions as a center for joint dhikr activities or pilgrimage activities in order to hope for ridho or for practical purposes, namely political interests in order to be given convenience in getting office.